The effects of GST knowledge towards students' spending pattern / Nurul Mardhiah Harun ... [et al.] - Harun, Nurul Mardhiah; Abd Hamid, Nadiah; Yahya, Mastora; Ahmad, Bedah; Ismail, Muhamad Irsaffuddin (2017)
The implementation of GST in Malaysia as of 1st April 2015, which replaced the current Sales and Services Tax (SST) is viewed as a more efficient tax to manage and is able to generate greater revenue collection for the government. This multi-tiered tax rate of 6 percent is finally borne by the end consumers of the goods and services regardless of their income levels. As a result, even non-income earners such as students are inevitably forced to bear the rising price of their consumptions. This study aimed to investigate the level of GST knowledge among the final year students in the Faculty of Accountancy, UiTM Puncak Alam. The students' knowledge and perception on issues related to GST were found to have certain impacts on their spending pattern. Evidently, the findings revealed that students who have much information about GST and in cases where they perceived that GST is an unfair and unequitable tax system, both situations are highly likely to have significant effects on their spending trend.